Introducing Microsoft SQL server 2012 - Mistry, Ross (Microsoft, 2015)
Microsoft SQL Server 2012 is Microsoft’s first cloud-ready information platform. It gives organizations effective tools to protect, unlock, and scale the power of their data, and it works across a variety of devices and data sources, from desktops, phones, and tablets, to datacenters and both private and public clouds. Our purpose in Introducing Microsoft SQL Server 2012 is to point out both the new and the improved capabilities as they apply to achieving mission-critical confidence, breakthrough insight, and using a cloud on your terms. As you read this book, we think you will find that there are a lot of exciting enhancements and new capabilities engineered into SQL Server 2012 that allow you to greatly enhance performance and availability at a low total cost of ownership, unlock new insights with pervasive data discovery across the organization and create business solutions fast—on your terms...